Modernists in Taos from Dasburg to Martin - Witt, David L. (Santa Fe, N.M. Red Crane Books, 2002)
"The northern New Mexico art communities of Taos and Santa Fe have played an important role in American art for a century. Taos in particular has served as a vital crossroad for American modernism. The time span from 1918 to 1979 defines the scope of this book because those six decades encompass the years of Andrew Dasburg's association with Taos. Also, the period generally corresponds to the era of American modernism. The emphasis in this book is on late modernism - that collection of modernist art movements that emerged following World War II. The war and its outcome was not only the twentieth century historic center of the United States, but important because nearly all of the late modernists in this book were part of the Greatest Generation
91362
Keywords: Taos school of art; Art, American -- New Mexico -- 20th century